Compound Heterozygous KCNQ1 Mutations Causing Recessive Romano–Ward Syndrome: Functional Characterization by Mutant Co-expression - González-Garrido, Antonia; Domínguez-Pérez, Mayra; Jacobo-Albavera, Leonor; López-Ramírez, Omar; Guevara-Chávez, José Guadalupe; Zepeda-García, Oscar; Iturralde, Pedro; Carnevale, Alessandra; Villarreal-Molina, Teresa (Frontiers in Cardiovascular Medicine, 2021)
Next Generation Sequencing has identified many KCNQ1 genetic variants associated with type 1 long QT or Romano-Ward syndrome, most frequently inherited in an autosomal dominant fashion, although recessive forms have been reported. Particularly in the case of missense variants, functional studies of mutants are of aid to establish variant pathogenicity and to understand the mechanistic basis of disease. Two compound heterozygous KCNQ1 mutations (p.A300T and p.P535T) were previously found in a child who suffered sudden death. To provide further insight into the clinical significance and basis for pathogenicity of these variants, different combinations of wildtype, A300T and P535T alleles were co-expressed with the accessory β-subunit minK in HEK293 cells, to analyze colocalization with the plasma membrane and some biophysical phenotypes of homo and heterotetrameric channels using the patch-clamp technique. A300T homotetrameric channels showed left-shifted activation V1/2 as previously observed in Xenopus oocytes, decreased maximum conductance density, slow rise-time300ms, and a characteristic use-dependent response. A300T slow rise-time300ms and use-dependent response behaved as dominant biophysical traits for all allele combinations. The P535T variant significantly decreased maximum conductance density and Kv7.1-minK-plasma membrane colocalization. P535T/A300T heterotetrameric channels showed decreased colocalization with plasma membrane, slow rise-time300ms and the A300T characteristic use-dependent response. While A300T left shifted activation voltage dependence behaved as a recessive trait when co-expressed with WT alleles, it was dominant when co-expressed with P535T alleles. Conclusions: The combination of P535T/A300T channel biophysical properties is compatible with recessive Romano Ward syndrome. Further analysis of other biophysical traits may identify other mechanisms involved in the pathophysiology of this disease.